INCIDENCE, CLINICAL PROFILE OF DIABETIC RETINOPATHY & ITS CORRELATION WITH GLYCEMIC CONTROL IN A TERTIARY CARE CENTER OF RAIGARH (CHHATTISGARH) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Diabetic retinopathy (DR) is a primary cause of avoidable blindness in the industrial regions of Chhattisgarh. Aim: To analyze the 3-year incidence, demographic trends, and clinical profile of DR in the Raigarh area. Methods: A hospital-based longitudinal observational study was conducted on 423 diabetic patients screened from 2023 to 2025. DR was graded using the International Clinical Diabetic Retinopathy (ICDR) scale. Results: The overall prevalence of DR was 21.28%. High-risk glycemic levels (PPBS > 200 mg/dl and HbA1c > 8.5%) showed a strong correlation with advanced DR stages. Conclusion: Systematic screening and lifestyle modification are essential to mitigate the burden of diabetic blindness in the district.